Potensi Reproduksi Induk Ternak Sapi Bali pada Sistem Peternakan Rakyat di Kecamatan Taniwel Timur Kabupaten Seram Bagian Barat - Siwa, I P; Souhoka, D F; Labetubun, J; Kewilaa, A I (Politeknik Negeri Lampung, 2024)
The reproductive performance of female Bali cattle is one of the important factors that needs to be known in supporting the efficiency of beef cattle breeding programs so that mothers can produce calves every year. This research aims to determine the characteristics of the reproductive potential of Bali cattle in the community farming system in East Taniwel District, West Seram Regency. The research location was determined purposively, selecting 6 sample villages from 15 villages in East Taniwel District, West Seram Regency based on the criteria of having the largest number of Balinese cattle. These villages are Sohuwe Village, Maloang Village, Matapa Village, Lumalatal Village, Sekasale Village and Hatunuru Village. The research was conducted for 1 month from August to September 2023. Respondents were determined using a purposive sampling method based on the presence of the highest number of cattle population per sample village and the highest level of Balinese cattle ownership with the criteria of having kept cattle for at least 3 years, had given birth and had carried out marketing. Farmer respondents were taken 10 respondents per sample village, so that 60 respondents were obtained. Data on the general condition of the research location, respondent characteristics, business characteristics, population structure and reproductive potential were analyzed using simple statistical calculations and studied descriptively. The research results show that the structure of the livestock population is dominated by the presence of female livestock at adult age, heifers and calves. The reproductive potential obtained is the age at first mating 18.16 ± 1.40 months; pregnancy rate 84.96%; and a birth rate of 99.43% with pre-weaning child mortality of 8.4%.